Leafminer egg distribution at decreasing leaf availability levels: Do females avoid intraspecific competition? - Aparicio, Maria Lourdes (2015)
Female ovipositing choices are expected to maximize offspring ﬁtness. Leafminers often lay their eggs in an aggregated fashion, leading to exploitative or interference competition among larvae. However, few studies have explored whether egg distribution patterns vary with leaf availability and whetherthese changes are an attempt to reduce competition effects on offspring ﬁtness. Here, we evaluated the egg distribution patterns of the specialist leafminer Liriomyza commelinae Frost (Diptera: Agromyzidae) for decreasing levels of leaf availability of their host plant Commelina erecta L. (Commelinaceae). Competition effects on insect performance were evaluated at various leaf larval densities in the laboratory and egg distribution was investigated for a wide range of leaf availability levels, both in the laboratory and in the ﬁeld. Liriomyza commelinae performance indicated that larvae competed forresources (exploitative competition), with a negative impact on survival and adult size at emergence when four or more larvae shared a leaf. The distribution of the immature stages of the leafminer was aggregated in both the laboratory and in the ﬁeld. As this pattern did not change with leaf availability,increasing levels of larval competition occurred when available leaves were scarce. Moreover, the proportion of total individuals subjected to the strongest competition level (six or more larvae per leaf) increased exponentially at the lower levels of leaf availability. Competition was found to be irrelevantas a selective force in shaping L. commelinae ovipositing decisions, as egg distribution was aggregated and did not vary with leaf availability, leading to relatively strong levels of competition. The egg distribution patterns observed in L. commelinae may have resulted from trade-offs between competition and factors such as enemy-free space and leaf quality.